PENINGKATAN PERAN SUKUK NEGARA DALAM PEMBIAYAAN INFRASTRUKTUR - Eri Hariyanto (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2021)
Sukuk Negara is one of the sharia-based financing instruments issued by the government to meet the budget deficit. This study aims to identify priority issues in the development of Sukuk Negara to enhance the role of Sukuk Negara in supporting government infrastructure financing. From the results of data management using the Analytic Network Process (ANP) method, it is known that several priority problems include the issuance of Sukuk Negara financing limited to central government projects, the lack of quality and quantity of Islamic finance human resources compared to conventional finance, and the low interest in public investment in Islamic financial instruments. The priority of the solution is the need to make regulations that allow Sukuk Negara to finance PPP project financing schemes, increase innovation and quality of sukuk products so that they are able to achieve the set targets, and foster public investment interest. Thus, the strategy in supporting the government's infrastructure development is to increase the proportion of SBSN issuance, increase socialization and communication to the public, and diversify underlying assets.